Analisis Penerapan Akuntansi Tarif Retribusi Daerah pada Pelayanan Kesehatan di Puskesmas Gunting Saga Kabupaten Labuhanbatu Utara - Madiha Putri Khairat Ritonga; Marliyah Marliyah; Arnida Wahyuni Lubis (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The main problem in this research is that the implementation of accounting for regional levies at the Gunting Saga Community Health Center is still not good. The aim of this research is to determine the application of regional levy rate accounting for health services at the Gunting Saga Community Health Center, North Labuhanbatu Regency. The method used in this research is a qualitative research method. Research techniques through interviews and documentation. The results of this research are that the implementation of the Gunting Saga Community Health Center's accounting can be said to be good, but it still needs to be developed and improved so that it complies with applicable accounting standards. The Gunting Saga Community Health Center has carried out the health service levy process well and collects fees in accordance with the health service rates that have been set in accordance with North Labuhanbatu Regency Regional Regulation (PERDA) Number 6 of 2022.